The Diario de Risaralda and its role in the Department of Risaralda creation. A look from the analysis frameworks (2019)
This article raises a historical-analytical look at the creationof the Department of Risaralda and the role played by thelocal press in this process in 1966 and 1967. An analysisframeworks methodology is applied and is also based ona discourse analysis, in order to review the case of thenewspaper Diario de Risaralda. It is concluded that thisnewspaper, was firmly linked as one of the main JuntaPro-Risaralda spokespersons media and the separatistcampaign to promote before the public opinion, apositive and legitimating message of a new departmentidea from three directions: a ) “El Occidente de Caldas”as a territory with historical cultural and economicrelations, facing the centralism of Manizales as a capitalcity; b) the creation of the Department of Risaralda as adecentralization and economic progress proposal; and c)the legitimation of a new departmental entity.